Marker-free fatigue crack detection and localization by integrating the optical flow and information entropy. (March 2023) - Xin, Cun; Wang, Cunjun; Xu, Zili; Wang, Jun; Yan, Song
Fatigue cracks caused by repetitive loads are one of the major threats to the structural integrity of civil infrastructure. Human inspection is the most common method for detecting fatigue cracks, but it is time-consuming, labor-intensive, and unreliable. In this paper, we propose a new vision-based fatigue crack detection and localization method that can detect the fatigue crack with marker-free and high precision using a consumer-grade digital camera. A motion tracking technology called optical flow algorithm is applied to the video for tracking the surface motion of the monitored structure under repetitive load. Then, a crack detection and localization algorithm based on optical flow information entropy are developed to search differential features at different video frames caused by the crack opening and closing. The proposed method's precision is first validated by doing two experiments and then comparing its precision and efficiency to the existing crack detection methods, including image processing and digital image correlation. The results show that, when compared to the existing vision-based methods, the proposed method can accurately and efficiently identify the fatigue crack even when the crack is surrounded by other crack-like edges, covered by complex surface textures, or invisible to human eyes. In addition, based on the proposed methods, a practical application for calculating the stress intensity factor is given to track crack development.